Caracterização do efeito whitening em polifluoreto de vinilideno (PVDF) por ensaio ultrassônico - Nascimento Filho, Emanuel Seixas (2017)
Polymeric materials are being increasingly used as engineering materials. In some polymers, the appearance of opaque areas is observed due to processing or mechanical stress. The appearance of these opaque regions is known as stress whitening. This study was intended to characterize qualitatively and quantitatively the whitening effect of polyvinylidene fluoride (PVDF) samples using the ultrasound test. Therefore, the techniques which used were the measurements of sonic velocity, spectral Fourier analysis, second order moment, Hurst analysis (R / S) and dentreded fluctutation analysis (DFA). Optical density measurements were performed to confirm and quantify the whitening effect on PVDF samples. Conventional techniques such as density measured by the Archimedes method was used as a comparative factor for the non-destructive techniques. The characterization of ultrasound was effective in characterizing the whitening effect. Quantitatively it was possible to characterize the whitening effect using sonic velocity measurements. The responses were obtained by the spectral Fourier analysis, second order moment, analyzes R / S and DFA managed to characterize the whitening effect qualitatively. In this study the optical density measurements have shown to be an excellent tool to characterize the whitening effect. The optical density test was possible to identify and quantify the whitening effect on PVDF samples.